Analysis of Law Enforcement in the Perspective of Law Number 32 of 2009 concerning Illegal Mining and Environmental Damage - Muhtadi, Muhamad Ammar; Surahmi , Mila; Saputra, Citra Dewi; Husin, Zaimah; Nasution, Emmi Rahmiwita (West Science Law and Human Rights, 2025)
This study investigates the enforcement of Law Number 32 of 2009 concerning Environmental Protection and Management, with a specific focus on addressing the phenomenon of illegal mining and its contribution to environmental degradation in Indonesia. Through a normative juridical approach, the research analyzes legal provisions, regulatory structures, and institutional mechanisms that govern environmental law enforcement. The findings reveal that although the law provides comprehensive tools—including administrative, civil, and criminal sanctions—its enforcement is often hindered by institutional fragmentation, weak monitoring systems, limited public participation, and political interference. Illegal mining continues to thrive in various regions, causing severe environmental damage such as deforestation, water pollution, and soil erosion. The study highlights the urgent need for integrated law enforcement, inter-agency coordination, legal reform, and community empowerment. Strengthening these areas is critical to realizing environmental justice and sustainability through effective legal implementation.